AVALIAÇÃO PSICOLÓGICA FORENSE E ÉTICA PROFISSIONAL - Santos, Rodrigo Soares; Andretta, Michelli Miranda; Couto, Gleiber (Revista PsicoFAE: Pluralidades em Saúde Mental, 2012)
O presente texto aborda a questão da produção de Laudos Psicológicos decorrentes de Avaliações Psicológicas Forenses e propõe uma reflexão com relação à ética profissional. Apresenta uma introdução ao tema da Psicologia Forense e dos processos éticos no Conselho Regional de Psicologia do Paraná; segue por um breve histórico referente à prova no processo penal, discorrendo, após, sobre a questão da Avaliação Psicológica Forense. Na sequência, são apresentados três estudos de caso: dois relativos a Inquéritos Policiais e um no âmbito da Vara de Família numa ação de Modificação de Guarda. Palavras-chave: Psicologia Forense; Avaliação Psicológica Forense; Laudos Psicológicos; Ética Profissional; Perícia Psicológica. ABSTRACT This paper addresses the question of production resulting from Psychological Reports Psychological Forensic Evaluations and proposes a reflection with respect to professional ethics. Provides an introduction to the subject of Forensic Psychology and ethical procedures in the Regional Council of Psychology of Parana; following provides a brief history regarding the evidence in criminal proceedings and after talks on the issue of Forensic Psychological Assessment. Following are three case studies: two relating to police investigations and in the Family Court in an action for Modification of Custody. Keywords: Forensic Psychology; Forensic Psychological Assessment; Psychological Reports; Professional Ethics; Psychological Expertise.